Enhanced susceptibility of obese mice to glycidamide‐induced sperm chromatin damage without increased oxidative stress. (30th August 2016) - Gutzkow, K. B.; Duale, N.; Danielsen, T.; von Stedingk, H.; Shahzadi, S.; Instanes, C.; Olsen, A.‐K.; Steffensen, I.‐L.; Hofer, T.; Törnqvist, M.; Brunborg, G.; Lindeman, B.
Summary: Diet‐induced obesity is known to impair male reproduction and may aggravate the male reproductive toxicity of the food contaminant acrylamide. Exposure of male mice to acrylamide induces paternally mediated pre‐ and post‐implantation losses because of spermatozoal toxicity and these effects are potentiated in mice fed a high‐fat diet. Glycidamide – an acrylamide metabolite – is the primary mediator of reproductive effects in males. The mechanisms causing the interaction between diet and acrylamide are not clear. However, diet‐induced obesity is associated with oxidative stress in male reproductive tissues which might contribute to increased germ cell susceptibility. In this study, we investigated whether a moderate diet‐induced obesity regimen could interfere with glycidamide‐induced spermatozoal toxicity and increase oxidative stress. For this purpose, sperm chromatin integrity, oxidised DNA and protein levels, transcript levels of oxidative stress responsive genes and glycidamide‐induced DNA and haemoglobin adducts were analysed in samples from male mice exposed to a high‐fat diet for 6 weeks in combination with a single glycidamide exposure 7 days prior to sacrifice. We found that glycidamide‐induced sperm DNA fragmentation was markedly higher in obese than in lean mice. However, the levels of oxidised DNA and/or protein in blood, liver and testicular tissue was lower in obese than in lean mice. Accompanying the reduced level of oxidised macromolecules, the transcript levels of several oxidative stress‐related genes were altered in the liver and testis from obese mice suggesting induction of an antioxidant response in these animals. The haemoglobin‐glycidamide adduct levels were higher in obese than in lean animals, whereas obesity did not seem to increase the level of glycidamide‐induced DNA adducts. These findings show that a moderate diet‐induced obesity regimen may potentiate glycidamide‐induced sperm cells toxicity and suggest that the increase in glycidamide‐induced sperm toxicity observed in obese mice does not depend on overt oxidative stress.